Identificación de los contaminantes atmosféricos emitidos por fuentes fijas en la elaboración de bloques de cemento en la parroquia Eloy Alfaro del cantón Latacunga, provincia de Cotopaxi, durante el período 2020-2021. - Sánchez Herrera, María José (2021)
The main objective of this investigation project is the identification of the atmospheric pollutants emitted by fixed resources in the manufacturing of cement blocks, stablished the area of study in four points with the greater influence in the Eloy Alfaro – Latacunga canton, according with the methodology stablished in the Current legal regulations about the quality of air and the maximum noise emission levels to fixes resources we realize the monitoring. We used the E-EBM equipment from particulate matter with continuous monitoring of 10 minutes during 48 hours, by each point. 24 hours to PM10 and 24 hours to PM2.5, which generated a data base in real time with the help of COMET software. To determinate of noise levels, we realized the day & night monitoring for each point with the sound level meter, to georeferenced the data obtained of the measurements we used the Geographic Information System. Registered values was compared with the Unified Text of Legislation of the Environment Ministry (TULSMA), Annex IV said that arithmetic average during 24 hours to PM10 should not exceed on hundred micrograms per cubic meter (100 〖 μg/m〗^3) and to PM2.5, should not exceed 100 〖μg/m〗^3 and to PM2.5 , should not exceed of 50 〖μg/m〗^3, the significant peaks of concentration for PM10 were registered in P1. Guapulo with 192 〖μg/m〗^3 and the PM2.5 in the P2. Patutan with 79 〖μg/m〗^3, however, all data of PM we are within the LMP. The points of affectation of environmental noise were registered in the day average (07:01 to 21:00) in the P2. Patutan with 69.0 dBA, and the night average (21:00 to 07:00) in the P4. La Calera with 77.7 dBA, the registered data in the evaluation of environment noise don’t accomplish with the regulation, so it exceeds the dBA night & day (55 dBA and 65 dBA) from TULSMA Annex V. The results obatined we determinated the prevention and mitigation strategies.